Music programming for psilocybin-assisted therapy: Guided Imagery and Music-informed perspectives - Messell, Catharina; Summer, Lisa; Bonde, Lars Ole; Beck, Bolette Daniels; Stenbæk, Dea Siggaard (Frontiers in Psychology, 2022)
The psychedelic drug psilocybin has been successfully explored as a novel treatment for a range of psychiatric disorders. Administration of psilocybin requires careful attention to psychological support and the setting in which the drug is administered. The use of music to support the acute psychoactive effects of psilocybin is recommended in current guidelines, but descriptions of how to compile music programs for the 4–6 h long sessions are still scarce. This article describes the procedural steps and considerations behind the curation of a new music program, the Copenhagen Music Program, tailored to the intensity profile of a medium/high dose psilocybin. The method of Guided Imagery and Music is presented as a music therapeutic framework for choosing and sequencing music in music programming and the Taxonomi of Therapeutic Music is presented as a rating tool to evaluate the music-psychological intensity of music pieces. Practical examples of how to organize the process of music programming are provided along with a full description of the Copenhagen Music Program and its structure. The aim of the article is to inspire others in their endeavours to create music programs for psychedelic interventions, while proposing that an informed music choice may support the therapeutic dynamics during acute effects of psilocybin.